Application of Multiple Intelligences Teaching Approach in Classroom Instruction - Sulaiman, Suriati (2011)
The aim of this research is to look at teachers’ instructional practices in employing multiple intelligences in classroom instruction. The main objective is to explore the application of multiple intelligences teaching approach in classroom instruction based on the POMAT model. Important aspects being explored include the application of multiple intelligences in instructional procedure, instructional objective, instructional material, classroom assessment and instructional technology. In order to meet the research objective, a qualitative study was developed. Research subjects were six English teachers who serve as informants. Data was collected from classroom observations, semi-structured in-depth interviews and document analysis. Classroom observations were conducted to record the actual classroom instruction that took place in English reading comprehension classrooms while semi-structured in-depth interviews were administered to obtain precise information from the informants. Raw data was recorded and transcribed manually. Later, the data was analysed interpretively and descriptively based on the themes that emerged from research findings. Triangulating data was done to ascertain the validity and reliability of the findings. Research findings reveal that the teachers do apply multiple intelligences teaching approach in classroom instruction even though most of the time they do it intuitively. Regardless of the fact, the teachers accommodate or reinforce two to seven intelligences in a single lesson. Three themes related to the application of multiple intelligences that are commonly employed in instructional procedure are: (1) instructional strategy based on verbal-linguistic intelligence; (2) instructional strategy based on interpersonal intelligence; and (3) instructional strategy based on bodily-kinaesthetic intelligence. The teachers construct instructional objectives based on learning outcome provided in the syllabus and curriculum specification. Two themes related to the application of multiple intelligences that are frequently employed in instructional objective are: (1) instructional objective based on verbal-linguistic intelligence; and (2) instructional objective based on interpersonal intelligence. One theme that emerges from the application of multiple intelligences that are regularly employed in instructional material is: (1) instructional material based on verbal- linguistic intelligence. One theme that transpires from the application of multiple intelligences that always employed in classroom assessment is: (1) assessment based on verbal-linguistic intelligence. Overall, the teachers are prone to apply verbal-linguistic intelligence in instructional procedure, instructional objective, instructional material and classroom assessment. It may work fine for students with natural verbal-linguistic strength but it may fail those who need to rely on other strengths to master the world of language learning. The findings also reveal that the teachers seldom integrate technology into their classroom instruction. Therefore, the teachers hardly employ any multiple intelligences in instructional technology. One theme that emerges from the application of multiple intelligences in instructional technology which hinders the teachers from integrating technology into classroom instruction is: (1) drawback. Sub-themes for drawback aspect that explains precisely reasons why the teachers cannot integrate technology into classroom instruction include: (1) time consuming; (2) inefficient lab management; (3) technical problems; and (4) no instructional technology expert. Based upon the insights gained from this study, it is recommended that teachers vary their instructional strategies used in classroom instruction to cater different intelligences, learning abilities, styles and needs of the students so that no students are left behind. Pedagogical implications of multiple intelligences teaching approach to classroom instruction have also been described. Above all, suggestions on how to apply multiple intelligences teaching approach in classroom instruction based on the POMAT model have been proposed in order to generate more effective classroom instruction. Finally, suggestions for future research have been recommended.